Peace is the way : writings on nonviolence from the Fellowship of Reconciliation - Wink, Walter (Maryknoll, N.Y. Orbis Books, 2000)
A collection of 55 essays related to all aspects of peace, non-violence and peace studies.
Keywords: Peace -- Religious aspects. Religion and justice